IL-17 signaling in keratinocytes orchestrates the defense against Staphylococcus aureus skin infection - Moos, Sonja; Regen, Tommy; Wanke, Florian; Tian, Yizhu; Arendholz, Lucas T.; Hauptmann, Judith; Heinen, André P.; Bleul, Lisa; Bier, Katharina; El Malki, Khalifa; Reinhardt, Christoph; Prinz, Immo; et al. (The journal of investigative dermatology, 2023)
Keratinocytes (KCs) form the outer epithelial barrier of the body, protecting against invading pathogens. Mice lacking the IL-17RA or both IL-17A and IL-17F develop spontaneous Staphylococcus aureus skin infections. We found a marked expansion of T17 cells, comprised of RORγt-expressing γδ T cells and T helper 17 cells in the skin-draining lymph nodes of these mice. Contradictory to previous suggestions, this expansion was not a result of a direct negative feedback loop because we found no expansion of T17 cells in mice lacking IL-17 signaling specifically in T cells. Instead, we found that the T17 expansion depended on the microbiota and was observed only when KCs were deficient for IL-17RA signaling. Indeed, mice that lack IL-17RA only in KCs showed an increased susceptibility to experimental epicutaneous infection with S. aureus together with an accumulation of IL-17A−producing γδ T cells. We conclude that deficiency of IL-17RA on KCs leads to microbiota dysbiosis in the skin, which triggers the expansion of IL-17A−producing T cells. Our data show that KCs are the primary target cells of IL-17A and IL-17F, coordinating the defense against microbial invaders in the skin.
Online verfügbar: 2. Februar 2023, Artikelversion: 21. Juni 2023
Gesehen am 23.08.2023